The Impact of Member Satisfaction on Sharia-Compliant Transaction Efficiency in Digital Islamic Cooperatives - Fahmi Halim, Andy; Aziz, Abdul (El-kahfi | Jurnal Ekonomi Islam, 2025)
This study investigates the effect of member satisfaction on Sharia-compliant transaction efficiency in KSBB Islamic Cooperative, highlighting the role of digital transformation in cooperative performance enhancement. Using a quantitative research design, data were collected from 100 active members of KSBB who utilized its digital platform. A structured questionnaire was employed to measure member satisfaction (usability, information quality, trust, and security) and transaction efficiency (time-cost effectiveness, accessibility, and Sharia compliance). Validity and reliability tests confirmed robust instrument quality (Cronbach’s α > 0.87). Classical assumption tests were satisfied, and simple linear regression was applied to analyze the relationship between variables. Results reveal that member satisfaction significantly predicts transaction efficiency (β = 0.678, p < 0.001), explaining 47.3% of its variance. This finding aligns with the Technology Acceptance Model (TAM) and Expectation Confirmation Theory (ECT), demonstrating that satisfaction derived from digital service quality enhances operational efficiency in Sharia-compliant contexts. The study also underscores the relevance of maqashid al-shariah, where efficiency supports hifz al-mal (wealth protection), amanah (trust), and maslahah (public welfare). External factors such as digital infrastructure, literacy, and cooperative management capacity are identified as additional determinants of efficiency beyond satisfaction. The research contributes to cooperative finance literature by integrating behavioral, operational, and ethical dimensions, offering empirical evidence that satisfaction-driven digitalization strengthens both efficiency and Sharia compliance in Islamic cooperatives. These findings provide strategic insights for policymakers and cooperative managers in advancing sustainable, digitally enabled Sharia-based cooperative systems.